Economic experience of the last fifteen years : Latin America and the Caribbean, 1980-1995 (ECLAC SantiagoCL, 1996)
Examines performance from the perspective of the link between the macroeconomic background and microeconomic behaviour, with particular emphasis on the institutions that provide the regulatory framework in which microeconomic activity takes place, and on the characteristics of the factor markets to which companies have access.
Bibliography: p. [119]-125